2006
DOI: 10.1021/tx0600550
|View full text |Cite
|
Sign up to set email alerts
|

Classification of a Diverse Set of Tetrahymena pyriformis Toxicity Chemical Compounds from Molecular Descriptors by Statistical Learning Methods

Abstract: Toxicity of various compounds has been measured in many studies by their toxic effects against Tetrahymena pyriformis. Efforts have also been made to use computational quantitative structure-activity relationship (QSAR) and statistical learning methods (SLMs) for predicting Tetrahymena pyriformis toxicity (TPT) at impressive accuracies. Because of the diversity of compounds and toxicity mechanisms, it is desirable to explore additional methods and to examine if these methods are applicable to more diverse sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 71 publications
5
61
0
1
Order By: Relevance
“…We further separated these compounds into training set and testing set by two different methods, 5-fold cross-validation and independent evaluation set, which have been widely used in the published ML compound prediction studies. [16][17][18][19][20]26,27 For 5-fold cross-validation, these compounds were randomly divided into five subsets with approximately equal size. Four subsets were arbitrarily chosen to form the training set to train the SVC model, and then the fifth subset was used as the testing set to examine the performance of the SVC model.…”
Section: Selection Of Antibacterial and Nonantibacterial Compoundsmentioning
confidence: 99%
See 3 more Smart Citations
“…We further separated these compounds into training set and testing set by two different methods, 5-fold cross-validation and independent evaluation set, which have been widely used in the published ML compound prediction studies. [16][17][18][19][20]26,27 For 5-fold cross-validation, these compounds were randomly divided into five subsets with approximately equal size. Four subsets were arbitrarily chosen to form the training set to train the SVC model, and then the fifth subset was used as the testing set to examine the performance of the SVC model.…”
Section: Selection Of Antibacterial and Nonantibacterial Compoundsmentioning
confidence: 99%
“…[16][17][18][19][20]26,27,[30][31][32][33][34] In this work, a group of 198 molecular descriptors was manually selected as the possible candidates from more than 1000 descriptors commonly described in the literature by roughly excluding those descriptors that are obviously redundant or irrelevant to the pharmacological and biological properties. These descriptors as described in the earlier studies 16,20 are given in Table 1, including 18 descriptors in the class of simple molecular properties, 27 descriptors in the class of molecular connectivity and shape, 97 descriptors in the class of electrotopological state, 31 descriptors in the class of quantum chemical properties, and 25 descriptors in the class of geometrical properties. The values of these descriptors were computed from the 3D structure of each compound by using our own developed molecular descriptor computing program.…”
Section: Molecular Descriptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many machine learning and data mining algorithms have been applied to study the structure-activity relationship of chemicals. For example, Xue et al reported promising results of applying five different machine learning algorithms: logistic regression, C4.5 decision tree, k-nearest neighbor, probabilistic neural network, and support vector machines to predicting the toxicity of chemicals against an organism of Tetrahymena pyriformis 21 .…”
Section: Introductionmentioning
confidence: 99%